Anti-corrosion paint for fire-fighting pipeline and preparation method of anti-corrosion paint

Through the fire-fighting pipeline anticorrosion paint composed of dispersants and dryers with specific ratios, the problem of poor anti-rust effect of existing coatings in high humidity and high salt environments is solved, and short drying time, low VOC emissions and excellent resistance are achieved. Impact performance meets the multi-faceted needs of fire-fighting pipe coatings.

CN119307165AInactive Publication Date: 2025-01-14HAIFENG MEIDA CHEM COATINGS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411574074.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing fire-fighting pipeline coatings are difficult to meet the requirements of various aspects such as rust prevention, weather resistance, color stability and environmental protection at the same time, especially in high humidity and high salt environments, and there are environmental pollution problems during the production and use of the coating.

Method used

Adopt anticorrosion paint consisting of alkyd resin, epoxy resin, modified barium sulfate, vapor phase silica, drying agent, etc., to achieve double stable dispersion and cross-linking of the paint through specific proportions of dispersants and drying agents. , shorten drying time, reduce VOC emissions, and improve impact and corrosion resistance.

Benefits of technology

The prepared anticorrosion paint has a short drying time, low VOC emissions, excellent impact resistance and corrosion resistance, meets environmental protection requirements, and improves the working efficiency and service life of the paint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005121306610000051
    Figure BDA0005121306610000051
  • Figure BDA0005121306610000081
    Figure BDA0005121306610000081
  • Figure BDA0005121306610000091
    Figure BDA0005121306610000091
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, and particularly discloses a fire-fighting pipeline anti-corrosion paint and a preparation method thereof. The invention discloses anti-corrosion paint for a fire-fighting pipeline. The anti-corrosion paint is prepared from a component A and a component B, the component A comprises alkyd resin, scarlet powder, 200 # solvent oil and a dispersing agent; the dispersing agent is formed by mixing an ammonium salt solution of an acrylate copolymer and tetrasodium iminodisuccinate; the component B comprises epoxy resin, modified barium sulfate, fumed silica, 200 # solvent oil, an anti-skinning agent and a drier; a preparation method of the modified barium sulfate comprises the following steps: mixing barium sulfate and carboxymethyl cellulose according to a weight ratio of 300: (8-20), carrying out hydrothermal reaction, drying and calcining to obtain the modified barium sulfate; the drier is formed by mixing zirconium naphthenate and a macromolecular organic sugar substance. The anti-corrosion paint prepared by the invention is short in drying time and low in VOC (Volatile Organic Compounds) emission, and the anti-corrosion paint has excellent impact resistance and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of coatings, and in particular to a fire protection pipeline anti-corrosion paint and a preparation method thereof. Background Art

[0002] As a key facility to ensure building safety, the performance of the anti-corrosion protective coating of fire protection pipes is crucial. Traditional fire protection pipe coatings are mostly paints or other organic coatings, which often expose the disadvantages of poor weather resistance, unsatisfactory anti-rust effect, and easy fading of color during long-term use. In addition, with the increasing global attention to environmental protection performance, harmful substances such as volatile organic compounds (VOCs) in traditional coatings have also become an important factor restricting their application.

[0003] The main problem faced by the existing technology is that most of the fire protection pipe coatings currently on the market cannot meet the requirements of rust prevention, weather resistance, color stability and environmental protection at the same time. Especially in harsh environments such as high humidity and high salt, the rust prevention effect of traditional coatings is greatly reduced, which seriously affects the service life and safety performance of fire protection pipes. At the same time, the environmental pollution problems caused by the production and use of coatings are becoming increasingly prominent and need to be solved urgently.

[0004] In response to the above problems, the industry has tried to develop a variety of new coatings, such as water-based coatings and high-solid coatings, to reduce VOCs emissions and improve anti-rust performance. However, these coatings still have many limitations in practical applications, such as slow drying speed and poor water resistance of water-based coatings; high-solid coatings face problems such as difficult construction and high cost. Therefore, these solutions have failed to fully meet the multi-faceted needs of fire pipe coatings. Therefore, the fire pipe coating industry faces the dual challenges of technological upgrading and environmental protection regulations. On the one hand, it is necessary to develop new coatings with better performance and better environmental protection to meet market demand; on the other hand, it is also necessary to adapt to increasingly stringent environmental protection regulations and reduce the environmental burden during production and use. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a fire protection pipe anti-corrosion paint and a preparation method thereof.

[0006] The present application provides a fire protection pipeline anticorrosive paint, which is composed of component A and component B in a weight ratio of 0.8-1.2:0.8-1.2; The A component specifically includes the following components in parts by weight: 550-610 parts of alkyd resin, 25-35 parts of red powder, 40-60 parts of 200# solvent oil, and 1.5-2.5 parts of dispersant; The dispersant is composed of a mixture of an ammonium salt solution of an acrylic acid ester copolymer and tetrasodium iminodisuccinate in a weight ratio of 10:0.5-2.0; The B component specifically includes the following components in parts by weight: 46-54 parts of epoxy resin, 220-280 parts of modified barium sulfate, 10-14 parts of fumed silica, 10-14 parts of 200# solvent oil, 6-10 parts of anti-skinning agent, and 5-7 parts of drying agent; The preparation method of the modified barium sulfate is as follows: barium sulfate and carboxymethyl cellulose are mixed in a weight ratio of 300:8-20, subjected to a hydrothermal reaction, dried, and then calcined to obtain the modified barium sulfate; The drying agent is composed of a mixture of zirconium cyclohexane acid and high molecular organic sugar material in a weight ratio of 8-15:0.5-1.5.

[0007] In this application, components A and B are mixed through the above-mentioned technical scheme to prepare anti-corrosion paint. The anti-corrosion paint prepared by this technical scheme has a short drying time, which is beneficial to improving work efficiency; and the anti-corrosion paint has low VOC emissions and good environmental protection; at the same time, the anti-corrosion paint has excellent impact resistance and corrosion resistance.

[0008] The anti-corrosion paint prepared in the present application is an alkyd resin paint system, and the dispersant used combines the steric hindrance effect of the ammonium salt solution of the acrylate copolymer and the charge neutralization ability of tetrasodium iminodisuccinate to achieve dual stable dispersion of the paint particles: the applicant optimizes the ratio of the two dispersants to achieve a synergistic improvement in the performance of the coating, so that the dispersion and bonding effect of the components in the coating is better, there is no microphase separation phenomenon, and the double bond groups and active groups in the resin are cross-linked with each other, which further promotes its oxidative polymerization reaction, ensures the curing and film-forming rate of the paint film, and greatly shortens the drying time of the anti-corrosion paint; and both substances have high biocompatibility and low toxicity, which is in line with the development trend of environmentally friendly coatings.

[0009] In component B, barium sulfate is modified by carboxymethyl cellulose to achieve uniform dispersion and compounding of barium sulfate and carbon, which can improve the surface polarity of barium sulfate and inhibit agglomeration while obtaining high dispersion of barium sulfate, thereby producing a coating with high filling properties, excellent hiding power and good impact resistance.

[0010] By combining zirconium naphthenate with high molecular organic sugar, a new type of composite drying agent is formed; this drying agent can not only effectively play the role of zirconium naphthenate in catalyzing the oxidative polymerization reaction of the coating, but also promote the cross-linking and curing of the coating through the introduction of high molecular organic sugar, and accurately adjust the addition amount and formula ratio of zirconium naphthenate and high molecular organic sugar to achieve a double drying effect, further improve the drying speed and coating quality of the coating, and the addition of high molecular organic sugar can effectively improve the flexibility of the coating, and the coating formed after drying is harder and more wear-resistant, with excellent impact resistance and corrosion resistance, effectively extending the service life of the coating. In addition, the composite drying agent composed of zirconium naphthenate and high molecular organic sugar has lower toxicity and volatility, and is more environmentally friendly.

[0011] Preferably, the fire protection pipe anticorrosive paint is composed of component A and component B in a weight ratio of 0.9-1.1:0.9-1.1; the component A specifically includes the following components in parts by weight: 560-600 parts of alkyd resin, 27-32 parts of red powder, 45-55 parts of 200# solvent oil, and 1.7-2.3 parts of dispersant; The B component specifically includes the following components in parts by weight: 48-52 parts of epoxy resin, 230-270 parts of modified barium sulfate, 11-13 parts of fumed silica, 11-13 parts of 200# solvent oil, 7-9 parts of anti-skinning agent, and 5.5-6.5 parts of drying agent.

[0012] Preferably, the dispersant is composed of a mixture of an ammonium salt solution of an acrylate copolymer and tetrasodium iminodisuccinate in a weight ratio of 10:0.8-1.5.

[0013] Preferably, the preparation method of the modified barium sulfate is: barium sulfate and carboxymethyl cellulose are mixed in a weight ratio of 300:10-18, 8-12 times by weight of water are added, and the mixture is kept warm for reaction at a temperature of 80-100°C for 6-16 hours; then cooled, solid-liquid separated, washed, and dried; then calcined at a temperature of 500-600°C for 3-5 hours; then cooled and ground to obtain the modified barium sulfate.

[0014] Preferably, the preparation method of the modified barium sulfate is: barium sulfate and carboxymethyl cellulose are mixed in a weight ratio of 300:10-18, 8-12 times by weight of water are added, and the mixture is kept warm for reaction at a temperature of 85-95°C for 8-12 hours; then cooled, solid-liquid separated, washed, and dried; then calcined at a temperature of 530-570°C for 3.5-4.5 hours; then cooled and ground to obtain the modified barium sulfate.

[0015] Preferably, in the drying agent, the high molecular weight organic sugar substance is selected from one or more of gum arabic, gelatin, xanthan gum and potassium alginate.

[0016] Preferably, the drying agent is composed of a mixture of zirconium cyclohexaneate and gum arabic in a weight ratio of 10-13:0.8-1.2.

[0017] Preferably, the anti-skinning agent is prepared by mixing 2,6-di-tert-butyl-4-methylphenol and vegetable oil in a weight ratio of 1-3:0.2-0.8.

[0018] 2,6-di-tert-butyl-4-methylphenol can effectively inhibit the occurrence of oxidation reactions in paint, thereby preventing the paint from forming skins due to oxidation during storage and use; this compound reacts with free radicals in the paint to interrupt the oxidation chain reaction, protect the paint from oxygen damage, and extend the service life of the paint. Vegetable oil mainly works through its good lubricity and film-forming properties. It can form a smooth film on the surface of the paint, reducing the surface area of ​​the paint in contact with air, thereby reducing the risk of oxidation skinning; at the same time, the unsaturated fatty acids in the vegetable oil can also react chemically with some components in the paint to generate stable compounds, further improving the paint's anti-skinning performance.

[0019] The combination of 2,6-di-tert-butyl-4-methylphenol and vegetable oil can give full play to the synergistic effect of the two and achieve a better anti-skinning effect; this compound anti-skinning agent can not only effectively inhibit oxidative skinning, but also improve the leveling and construction performance of the coating, and improve the gloss and weather resistance of the coating. Therefore, add an appropriate amount of 2,6-di-tert-butyl-4-methylphenol and vegetable oil to the coating as an anti-skinning agent.

[0020] On the other hand, the present application provides a method for preparing the above-mentioned fire protection pipe anticorrosive paint, which specifically comprises the following steps: at a rotation speed of 250-350 rpm, 550-610 parts of alkyd resin, 25-35 parts of red powder, 40-60 parts of 200# solvent oil, and 1.5-2.5 parts of dispersant are added in sequence, and after stirring at 1000-1400 rpm for 25-35 minutes, the mixture is ground by a sand mill to less than 20 μm to obtain component A; At a rotation speed of 700-900 rpm, 46-54 parts of epoxy resin, 220-280 parts of superfine barium sulfate, 10-14 parts of fumed silica, 10-14 parts of 200# solvent oil, 6-10 parts of anti-skinning agent, and 5-7 parts of drying agent were added in sequence, and stirred at 1000-1400 rpm for 10-20 minutes to obtain component B; At a rotation speed of 700-900 rpm, add the B component to the A component, and stir at 1000-1400 rpm for 10-20 min to obtain the product.

[0021] In summary, the technical solution of this application has the following effects: The present application utilizes a mixture of an ammonium salt solution of an acrylate copolymer and tetrasodium iminodisuccinate in a specific weight ratio to form a dispersant, which is mixed with a specific amount of alkyd resin, red powder, and 200# solvent oil as component A of the paint; at the same time, a mixture of zirconium cyclohexaneate and a high-molecular organic sugar substance in a specific weight ratio to form a drying agent, which is mixed with a specific amount of modified barium sulfate, epoxy resin, fumed silica, 200# solvent oil, and an anti-skinning agent as component B of the paint; then components A and B are mixed to prepare an anti-corrosion paint. The anti-corrosion paint prepared by this technical solution has a short drying time, which is beneficial to improving work efficiency; and the anti-corrosion paint has low VOC emissions and good environmental protection; at the same time, the anti-corrosion paint has excellent impact resistance and corrosion resistance. DETAILED DESCRIPTION

[0022] The present application is further described in detail below in conjunction with examples, comparative examples and performance testing experiments. These examples should not be construed as limiting the scope of protection claimed in the present application.

[0023] Alkyd resin, CAS No. 63148-69-6; red powder (model PR254) was purchased from Lily; ammonium salt solution of acrylate copolymer (model BYK-155) was purchased from BYK, Germany; carboxymethyl cellulose (MF-004110) was purchased from Xinyang Mufan Biotechnology Co., Ltd.; gum arabic (item number S52903), gelatin (item number S30952), and potassium alginate (CAS number 9005-36-1) were purchased from Shanghai Yuanye Biotechnology Co., Ltd.; soybean oil was purchased from Jishui County Yikang Natural Spice Oil Refinery.

[0024] The remaining raw materials and reagents can be obtained commercially. Example

[0025] Examples 1-5 Embodiments 1-5 respectively provide a fire protection pipe anticorrosive paint and a preparation method thereof.

[0026] The difference between the above embodiments is that the dosage of each component in the fire protection pipe anti-corrosion paint is different, as shown in Table 1.

[0027] The preparation method of the fire protection pipeline anticorrosive paint in the above embodiment is: Preparation of modified barium sulfate: 300 g of barium sulfate and 14 g of carboxymethyl cellulose are mixed in a weight ratio of 300:14, 10 times the weight of water is added, and the mixture is kept warm at 90°C for 10 hours; then cooled, solid-liquid separated, washed with water, and dried; then calcined at 550°C for 4 hours; then cooled and ground to less than 5 μm to obtain modified barium sulfate.

[0028] At a rotation speed of 300 rpm, alkyd resin, red powder, 200# solvent oil, and dispersant (composed of a mixture of an ammonium salt solution of an acrylate copolymer and tetrasodium iminodisuccinate in a weight ratio of 10:1.5) were added in sequence, stirred at 1200 rpm for 30 minutes, and then ground with a sand mill to less than 20 μm to obtain component A; At a rotation speed of 800 rpm, bisphenol A epoxy resin (E-51), modified barium sulfate, fumed silica, 200# solvent oil, anti-skinning agent (mixed with 2,6-di-tert-butyl-4-methylphenol and soybean oil in a weight ratio of 2:0.5), and drying agent (mixed with zirconium cyclohexane acid and gum arabic high molecular organic sugar in a weight ratio of 12:1) were added in sequence, and after stirring at 1200 rpm for 15 minutes, component B was obtained; At a rotation speed of 800 rpm, add component B to component A in a weight ratio of 1:1, and stir at 1200 rpm for 15 minutes to obtain the fire protection pipe anti-corrosion paint.

[0029] Table 1 The amount of each component in the fire protection pipeline anticorrosive paint in Examples 1-5 and Comparative Examples 1-2 Embodiment 6-7 Examples 6-7 respectively provide a fire protection pipe anti-corrosion paint and a preparation method thereof.

[0030] The difference between the above embodiment and embodiment 1 is that the type of dispersant is different, as shown below.

[0031] In Example 6: the dispersant is composed of a mixture of an ammonium salt solution of an acrylate copolymer and tetrasodium iminodisuccinate in a weight ratio of 10:0.5.

[0032] In Example 7: the dispersant is composed of a mixture of an ammonium salt solution of an acrylate copolymer and tetrasodium iminodisuccinate in a weight ratio of 10:2.0.

[0033] The remaining process parameters in the above embodiment are the same as those in embodiment 1.

[0034] Embodiment 8-11 Examples 8-11 respectively provide a fire protection pipe anti-corrosion paint and a preparation method thereof.

[0035] The difference between the above embodiment and embodiment 1 is that the preparation method of modified barium sulfate is different, as shown below.

[0036] In Example 8: The preparation method of modified barium sulfate is as follows: 300 g of barium sulfate and 8 g of carboxymethyl cellulose are mixed in a weight ratio of 300:8, 10 times the weight of water is added, and the mixture is kept warm at 80°C for 6 hours; then cooled, solid-liquid separated, washed with water, and dried; then calcined at 550°C for 4 hours; then cooled and ground to less than 5 μm to obtain modified barium sulfate.

[0037] In Example 9: The preparation method of modified barium sulfate is as follows: 300 g of barium sulfate and 20 g of carboxymethyl cellulose are mixed in a weight ratio of 300:20, 10 times the weight of water is added, and the mixture is kept warm at 90°C for 10 hours; then cooled, solid-liquid separated, washed with water, and dried; then calcined at 450°C for 4 hours; then cooled and ground to less than 5 μm to obtain modified barium sulfate.

[0038] In Example 10: The preparation method of modified barium sulfate is as follows: 300 g of barium sulfate and 10 g of carboxymethyl cellulose are mixed in a weight ratio of 300:20, 10 times the weight of water is added, and the mixture is kept warm at 90°C for 10 hours; then cooled, solid-liquid separated, washed with water, and dried; then calcined at 500°C for 4 hours; then cooled and ground to less than 5 μm to obtain modified barium sulfate.

[0039] In Example 11: The preparation method of modified barium sulfate is as follows: 300 g of barium sulfate and 10 g of carboxymethyl cellulose are mixed in a weight ratio of 300:18, 10 times the weight of water is added, and the mixture is kept warm at 90°C for 10 hours; then cooled, solid-liquid separated, washed with water, and dried; then calcined at 600°C for 4 hours; then cooled and ground to less than 5 μm to obtain modified barium sulfate.

[0040] The remaining process parameters in the above embodiment are the same as those in embodiment 1.

[0041] Examples 12-16 Examples 12-16 respectively provide a fire protection pipe anti-corrosion paint and a preparation method thereof.

[0042] The difference between the above embodiment and embodiment 1 is that the types of drying agents are different, as shown below.

[0043] In Example 12: the drying agent is composed of a mixture of zirconium cyclohexaneate and gelatin in a weight ratio of 12:1.

[0044] In Example 13: the drying agent is composed of a mixture of zirconium cyclohexaneate and potassium alginate in a weight ratio of 12:1.

[0045] In Example 14: the drying agent is composed of a mixture of zirconium cyclohexaneate and gum arabic high molecular organic sugar in a weight ratio of 8:1.5.

[0046] In Example 15: the drying agent is composed of a mixture of zirconium cyclohexaneate and gum arabic high molecular organic sugar in a weight ratio of 10:1.2.

[0047] In Example 16: the drying agent is composed of a mixture of zirconium cyclohexaneate and gum arabic high molecular organic sugar in a weight ratio of 13:0.8.

[0048] The remaining process parameters in the above embodiment are the same as those in embodiment 1.

[0049] Examples 17-20 Examples 17-20 respectively provide a fire protection pipe anti-corrosion paint and a preparation method thereof.

[0050] The difference between the above embodiment and embodiment 1 is that the types of anti-skinning agents are different, as shown below.

[0051] In Example 17: the anti-skinning agent is 2,6-di-tert-butyl-4-methylphenol.

[0052] In Example 18: the anti-skinning agent is prepared by mixing 2,6-di-tert-butyl-4-methylphenol and soybean oil in a weight ratio of 2:0.5.

[0053] In Example 19: the anti-skinning agent is prepared by mixing 2,6-di-tert-butyl-4-methylphenol and soybean oil in a weight ratio of 1:0.8.

[0054] In Example 20: the anti-skinning agent is prepared by mixing 2,6-di-tert-butyl-4-methylphenol and soybean oil in a weight ratio of 3:0.2.

[0055] The remaining process parameters in the above embodiment are the same as those in embodiment 1.

[0056] Comparative Example Comparative Example 1-2 Comparative Examples 1-2 respectively provide a fire protection pipe anti-corrosion paint and a preparation method thereof.

[0057] The difference between the comparative example and Example 1 is that the dosage of each component in the fire protection pipe anticorrosive paint is different, as shown in Table 1.

[0058] The remaining process parameters in the above comparative example are the same as those in Example 1.

[0059] Comparative Examples 3-5 Comparative Examples 3-5 respectively provide a fire protection pipe anti-corrosion paint and a preparation method thereof.

[0060] The difference between the above comparative example and Example 1 is as follows.

[0061] In Comparative Example 3: the dispersant is composed of a mixture of an ammonium salt solution of an acrylate copolymer and tetrasodium iminodisuccinate in a weight ratio of 10:3.

[0062] In Comparative Example 4: an equal amount of unmodified barium sulfate was used to replace the modified barium sulfate.

[0063] In Comparative Example 5, the drying agent is composed of a mixture of zinc cyclohexaneate and gum arabic in a weight ratio of 12:1.

[0064] The remaining process parameters in the above comparative example are the same as those in Example 1.

[0065] Performance testing (1) Drying speed: Test and record the surface drying time and actual drying time of the anticorrosive paint in accordance with GB / T 1728; (2) Impact resistance: tested in accordance with the method specified in GB / T 20624.2-2006; (3) VOC emissions: tested in accordance with the method specified in GB / T 18582-2008; (4) Water resistance: Test the water resistance of the anti-corrosion paint in accordance with GB / T 1733-1993; observe phenomena such as blistering, rusting, cracking, and peeling.

[0066] (5) Salt water resistance: Test the salt water resistance of the anti-corrosion paint in accordance with GB / T 25251-2010; observe phenomena such as blistering, rusting, cracking, and peeling.

[0067] Test results: as shown in Table 2.

[0068] Table 2 Performance test results of fire protection pipeline anticorrosive paint in the embodiments and comparative examples Combined with the test results in Table 2, the present application uses a mixture of an ammonium salt solution of an acrylate copolymer and tetrasodium iminodisuccinate in a weight ratio of 10:0.5-2.0 to form a dispersant, and a specific amount of alkyd resin, red powder, and 200# solvent oil as the A component of the paint; at the same time, a zirconium cyclohexane acid and a high molecular organic sugar substance in a weight ratio of 8-15:0.5-1.5 are mixed to form a drying agent, and a specific amount of modified barium sulfate, epoxy resin, fumed silica, 200# solvent oil, and an anti-skinning agent are used as the B component of the paint; then the A and B components are mixed to prepare an anti-corrosion paint. The anti-corrosion paint prepared by this technical solution has a short drying time, which is beneficial to improving work efficiency; and the anti-corrosion paint has low VOC emissions and good environmental protection; at the same time, the anti-corrosion paint has excellent impact resistance and corrosion resistance.

[0069] By comparing the test results of Examples 1-5 with Comparative Examples 1-2, the amounts of the raw material components in Comparative Examples 1-2 are not matched, and the comprehensive performance of the anticorrosive paint prepared is poor. In contrast, the present application effectively ensures the comprehensive performance of the paint by optimizing and matching the amounts of the raw materials in components A and B.

[0070] By comparing the test results of Examples 1, 6-7 with Comparative Example 3, the dispersant in Comparative Example 3 is composed of a mixture of an ammonium salt solution of an acrylate copolymer and tetrasodium iminodisuccinate at a weight ratio of 10:3, the drying time of the anticorrosive paint is long, and the impact resistance of the paint is poor. In contrast, the present application uses a mixture of an ammonium salt solution of an acrylate copolymer and tetrasodium iminodisuccinate at a weight ratio of 10:0.5-2.0 to form a dispersant, which effectively improves the comprehensive performance of the paint.

[0071] By comparing the test results of Examples 1, 8-11 with Comparative Example 4, in Comparative Example 4, unmodified barium sulfate was used instead of modified barium sulfate, and the impact resistance and salt water resistance of the paint were poor. In contrast, the present application mixed barium sulfate and carboxymethyl cellulose in a weight ratio of 300:8-20, subjected to hydrothermal reaction, dried and then calcined to obtain modified barium sulfate as a raw material, which effectively improved the comprehensive performance of the paint.

[0072] By comparing the test results of Examples 1, 12-16 with Comparative Example 5, the drying agent in Comparative Example 5 is composed of a mixture of zinc cyclohexane acid and gum arabic in a weight ratio of 12:1, the anticorrosive paint has a long drying time, a high VOC emission, and poor impact resistance and salt water resistance of the paint. In contrast, the present application comprises a mixture of zirconium cyclohexane acid and a high molecular organic sugar substance in a weight ratio of 8-15:0.5-1.5 to form a drying agent, which effectively improves the comprehensive performance of the paint.

[0073] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A fire protection pipeline anticorrosive paint, characterized in that: It is composed of component A and component B in a weight ratio of 0.8-1.2:0.8-1.2; The A component specifically includes the following components in parts by weight: 550-610 parts of alkyd resin, 25-35 parts of red powder, 40-60 parts of 200# solvent oil, and 1.5-2.5 parts of dispersant; The dispersant is composed of a mixture of an ammonium salt solution of an acrylic acid ester copolymer and tetrasodium iminodisuccinate in a weight ratio of 10:0.5-2.0; The B component specifically includes the following components in parts by weight: 46-54 parts of epoxy resin, 220-280 parts of modified barium sulfate, 10-14 parts of fumed silica, 10-14 parts of 200# solvent oil, 6-10 parts of anti-skinning agent, and 5-7 parts of drying agent; The preparation method of the modified barium sulfate is as follows: barium sulfate and carboxymethyl cellulose are mixed in a weight ratio of 300:8-20, subjected to a hydrothermal reaction, dried, and then calcined to obtain the modified barium sulfate; The drier is composed of 8-15 weight ratio: It is composed of a mixture of 0.5-1.5% zirconium cyclohexaneate and high molecular weight organic sugar substances.

2. The fire protection pipe anticorrosive paint according to claim 1, characterized in that: It is composed of component A and component B in a weight ratio of 0.9-1.1:0.9-1.1; The A component specifically includes the following components in parts by weight: 560-600 parts of alkyd resin, 27-32 parts of red powder, 45-55 parts of 200# solvent oil, and 1.7-2.3 parts of dispersant; The B component specifically includes the following components in parts by weight: 48-52 parts of epoxy resin, 230-270 parts of modified barium sulfate, 11-13 parts of fumed silica, 11-13 parts of 200# solvent oil, 7-9 parts of anti-skinning agent, and 5.5-6.5 parts of drying agent.

3. The fire protection pipeline anticorrosive paint according to claim 1, characterized in that: The dispersant is composed of a mixture of an ammonium salt solution of an acrylic acid ester copolymer and tetrasodium iminodisuccinate in a weight ratio of 10:0.8-1.

5.

4. The fire protection pipeline anticorrosive paint according to claim 1, characterized in that: The preparation method of the modified barium sulfate is as follows: barium sulfate and carboxymethyl cellulose are mixed in a weight ratio of 300:10-18, 8-12 times by weight of water are added, and the mixture is kept warm for reaction at a temperature of 80-100°C for 6-16 hours; then cooled, solid-liquid separated, washed, and dried; then calcined at a temperature of 500-600°C for 3-5 hours; then cooled and ground to obtain the modified barium sulfate.

5. The fire protection pipeline anticorrosive paint according to claim 4 is characterized in that: The preparation method of the modified barium sulfate is as follows: barium sulfate and carboxymethyl cellulose are mixed in a weight ratio of 300:10-18, 8-12 times of water are added, and the mixture is kept warm for reaction at a temperature of 85-95° C. for 8-12 hours; then cooled, solid-liquid separated, washed, and dried; and then calcined at a temperature of 530-570° C. for 3.5-4.5 hours; Then cooling and grinding are carried out to obtain the modified barium sulfate.

6. The fire protection pipeline anticorrosive paint according to claim 1, characterized in that: In the drying agent, the high molecular weight organic sugar substance is selected from one or more of gum arabic, gelatin, xanthan gum and potassium alginate.

7. The fire protection pipeline anticorrosive paint according to claim 6, characterized in that: The drier is composed of a weight ratio of 10-13: 0.8-1.2 of zirconium cyclohexaneate and gum arabic are mixed.

8. The fire protection pipeline anticorrosive paint according to claim 1, characterized in that: The anti-skinning agent is prepared by mixing 2,6-di-tert-butyl-4-methylphenol and vegetable oil.

9. The fire protection pipeline anticorrosive paint according to claim 8, characterized in that: The anti-skinning agent is prepared by mixing 2,6-di-tert-butyl-4-methylphenol and vegetable oil in a weight ratio of 1-3:0.2-0.

8.

10. The method for preparing the fire protection pipeline anticorrosive paint according to any one of claims 1 to 9, characterized in that: The specific steps include: At a rotation speed of 250-350 rpm, 550-610 parts of alkyd resin, 25-35 parts of red powder, 40-60 parts of 200# solvent oil, and 1.5-2.5 parts of dispersant were added in sequence, stirred at 1000-1400 rpm for 25-35 minutes, and then ground with a sand mill to less than 20 μm to obtain component A; At a rotation speed of 700-900 rpm, 46-54 parts of epoxy resin, 220-280 parts of superfine barium sulfate, 10-14 parts of fumed silica, 10-14 parts of 200# solvent oil, 6-10 parts of anti-skinning agent, and 5-7 parts of drying agent were added in sequence, and stirred at 1000-1400 rpm for 10-20 minutes to obtain component B; Under the condition of a rotation speed of 700-900 rpm, the B component is added to the A component, and stirred at 1000-1400 rpm for 10-20 min to obtain the product.